2013
DOI: 10.4172/2155-6156.1000259
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Homocysteine as Predictors of Pre-eclampsia

Abstract: Objective: To estimate the serum homocysteine and uric acid levels in normal and pre-eclamptic patients and to find out any correlation between these parameters and pre-eclampsia Study design and setting: Cross-sectional study; Dept. of Biochemistry in collaboration with Department of Obstetrics and Gynaecology, Regional Institute of Medical Sciences (RIMS); Imphal (Manipur), India.Methods: Data collected from 50 pre-eclamptic pregnant women and 25 normotensive pregnant women admitted in Antenatal ward, Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…18 Almost similar findings were also observed in some other studies. [19][20][21] In the current study, it was observed that the mean serum homocysteine was 16.4±7.9 µmol/l in mild preeclampsia, 20.8±8.0 µmol/l in severe preeclampsia and 8.2±3.7 µmol/l in normal pregnant group.A study conducted by Yelikar and colleagues found the mean serum homocysteine levels in mild preeclampsia, severe preeclampsia was 14.99±3.47 µmol/l and 19.90±6.17 µmol/l and 12.48±2.95 µmol/l in normal pregnancy. 18 The study conducted by Ferdausi and colleagues found the mean serum homocysteine levels in mild preeclampsia, severe preeclampsia was 10.43±5.12 mol/l and 11.5±4.58 mol/l and 5.70±1.30 mol/L in normal pregnancy.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…18 Almost similar findings were also observed in some other studies. [19][20][21] In the current study, it was observed that the mean serum homocysteine was 16.4±7.9 µmol/l in mild preeclampsia, 20.8±8.0 µmol/l in severe preeclampsia and 8.2±3.7 µmol/l in normal pregnant group.A study conducted by Yelikar and colleagues found the mean serum homocysteine levels in mild preeclampsia, severe preeclampsia was 14.99±3.47 µmol/l and 19.90±6.17 µmol/l and 12.48±2.95 µmol/l in normal pregnancy. 18 The study conducted by Ferdausi and colleagues found the mean serum homocysteine levels in mild preeclampsia, severe preeclampsia was 10.43±5.12 mol/l and 11.5±4.58 mol/l and 5.70±1.30 mol/L in normal pregnancy.…”
Section: Discussionsupporting
confidence: 53%
“…24 In this present study there is a significant positive correlation (r=0.455; p=0.001) was found between systolic blood pressure with serum homocysteine level.Othersimilar studies showed a positive correlation between serum homocysteine and systolic blood pressure. 16,19,25 . The above findings are closely resembled with the present study.In this present study significant positive correlation (r=0.546, p=0.001) was also found between diastolic blood pressure with serum homocysteine level, which is similar with some other studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sangeeta et al [19], the cause of hyperuricemia in preeclampsia is attributed to either a decreased excretion or to an increased production of uric acid.…”
Section: Discussionmentioning
confidence: 99%